A description of the larva of Coomaniella (Coomaniella) purpurascens Baudon, 1966 and a discussion on the tribal placement of Coomaniellini Bílý, 1974 (Coleoptera: Buprestidae) - Bílý, Svatopluk; Volkovitsh, Mark G. (Zootaxa, 2015)
A detailed description of the mature larva of Coomaniella (Coomaniella) purpurascens Baudon, 1966 and a discussion of the taxonomic position of the tribe Coomaniellini Bílý, 1974 are presented. Larva is fully illustrated including details of the mouth parts and inner structures of the proventriculus. The larval characters support the tribal status of Coomaniellini with close relations to the tribe Dicercini Gistel, 1884 in contrast with the former placement of the tribe near Anthaxiini Gory & Laporte, 1839.